The Influence of Electronic Word-of-Mouth Communication and Delay of Gratification on Online Impulsive Buying Behavior among Student Users of Shopee E-Commerce Platform in Bandung Raya - Nurul Fitriani Fatonah; Aqmal Maulana Saputra (IJIP : Indonesian Journal of Islamic Psychology, 2025)
The rapid growth of e-commerce in Indonesia has triggered a surge in online impulsive buying behavior (OIBB), particularly among university students as digital natives. This phenomenon can lead to negative consequences such as financial problems, regret, and impaired psychological well-being. This study aims to examine the effects of Electronic Word of Mouth (eWOM) and Deferment of Gratification (DoG) on OIBB among active Shopee users in the Greater Bandung area, using a quantitative regression approach with 110 respondents. The regression results show that the research model explains 59.4% of the variance in OIBB (Adjusted R² = 0.594). Partially, eWOM has a significant positive effect on OIBB (β = 0.553; p < 0.001), while DoG has a significant negative effect (β = –0.327; p < 0.001). These results indicate that higher exposure to eWOM increases the tendency for OIBB, whereas the ability to defer gratification can reduce such behavior. The findings provide practical benefits for individuals to enhance self-awareness, manage impulsive online shopping urges, and cultivate wiser and more controlled online shopping habits.